Parent and nurse perceptions on the quality of family-centred care in 11 European NICUs. Issue 4 (November 2016) - ,; Raiskila, Simo; Lehtonen, Liisa; Tandberg, Bente Silnes; Normann, Erik; Ewald, Uwe; Caballero, Sylvia; Varendi, Heili; Toome, Liis; Nordhøv, Marianne; Hallberg, Boubou; Westrup, Björn; et al.
Abstract: Background: Family-centred care (FCC) is a state-of-the-art practice in neonatal intensive care units (NICU) based on its shown benefits on the well-being of both infants and parents. However, there is no systematic knowledge about how FCC is implemented in different European contexts. Objectives: To describe parents' presence and the quality of FCC from the perspectives of mothers, fathers and nurses in 11 European NICUs. Methods: A prospective survey was conducted in Finland, Sweden, Norway, Estonia, Spain and Italy. The perceived quality of FCC was measured using 8 text-message questions sent to the parents' mobile phones, one question each day, during the infant's hospital stay. Nurses answered corresponding questions through a Web questionnaire during a 3-month period. The responses were rated on a 7-point Likert scale. Parents who were not present in the unit during the day used a "0" response. Results: A total of 262 families of preterm infants born before 35 gestational weeks participated in the study. Mothers gave 5045 responses, fathers gave 3971 responses and nurses gave 11, 132 answers. The mothers were present during 92.7% and the fathers during 77.9% of the study days. The mothers rated the quality of FCC slightly higher than the fathers did (5.8 [95% CI 5.7–5.9] vs. 5.7 [95% CI 5.6–5.8], mean difference of 0.12 [95% CI 0.05–0.2], p  < 0.001). There was wide variation in the parents' presence and the quality of FCC between the units. The weakest aspects of FCC were emotional support, parents' participation in decision-making and fathers' participation in infant care. The perceived quality of FCC between the nurses and parents were comparable. Conclusions: This study showed a high perceived quality of FCC in 11 European units, as indicated by both parents and nurses. The innovative data-collection method and instrument successfully quantified each unit's FCC profile for further quality improvement and should be trialled in other NICUs and countries.